Scatter gram patterns of hematological malignancies in Sysmex XN series - Kovuri Umadevi; Lavanya Motrapu; Mohd Imran Ali; Rajarikam Nagarjunachary; Seshava Puri Smitha Vadana (Asian Journal of Medical Sciences, 2023)
Background: Scatter grams-graphic depictions of the cell populations in a blood sample are produced by automated analyzers. These scatter grams can be employed to screen for various hematological conditions, including anemia, leukemia, and other blood disorders by examining the scatter gram’s cell population distribution and patterning. Aims and Objectives: In this study, we wish to study the scatter grams generated by the Sysmex XN-series analyzer for confirmed cases of hematological malignancies. Materials and Methods: In this study, 58 cases of hematologic malignancies diagnosed based on peripheral smear findings and bone marrow morphology data were extracted. We retrieved the complete blood count and scatter gram patterns analyzed by Sysmex XN-1000 analyzer for these cases along with peripheral smear findings. Scatter gram patterns in white blood cell differential and white cell nucleated were analyzed correlating with peripheral smears. Results: Among 58 cases, 20 cases were acute myeloid leukemia (6 were acute promyelocytic leukemia), 32 cases were chronic myeloid leukemia, and 5 cases were chronic lymphocytic leukemia. Unique scatter gram patterns were seen with different leukemias. Conclusion: Pattern analysis of scatter grams has the potential to improve the efficiency and accuracy of leukemia diagnosis and also help to prioritize the evaluation of cases that require further testing, such as molecular and cytogenetic evaluations, especially in limited resources or high sample volumes conditions.